North Atlantic storm track changes during the Last Glacial Maximum recorded by Alpine speleothems - Luetscher, Marc; Boch, Ronny; Sodemann, Harald; Spötl, Christoph; Cheng, Hai; Edwards, Roger Lawrence; Frisia, Silvia; Hof, Florian; Müller, Wolfgang A. (Nature Communications, 2015)
The European Alps are an effective barrier for meridional moisture transport and are thus uniquely placed to record shifts in the North Atlantic storm track pattern associated with the waxing and waning of Late-Pleistocene Northern Hemisphere ice sheets. The lack of well-dated terrestrial proxy records spanning this time period, however, renders the reconstruction of past atmospheric patterns difficult. Here we present a precisely dated, continuous terrestrial record of meteoric precipitation in Europe between 30 and 14.7 ka. In contrast to present-day conditions, our speleothem data provide strong evidence for preferential advection of moisture from the South across the Alps supporting a southward shift of the storm track during the local Last Glacial Maximum (that is, 26.5–23.5 ka). Moreover, our age control indicates that this circulation pattern preceded the Northern Hemisphere precession maximum by ~3 ka, suggesting that obliquity may have played a considerable role in the Alpine ice aggradation. publishedVersion